Understanding the nature and dynamics of Mycobacterium ulcerans cytochrome P450 monooxygenases (CYPs) – a bioinformatics approach - Sur, Saubashya (Acta Biologica Szegediensis, 2021)
Cytochrome P450 monooxygenases (CYPs or P450s) are catalytically versatile hemoproteins, associated with drug metabolism, substrate utilization and pathogenesis. Mycobacterium ulcerans is a human pathogen causing Buruli ulcer. The study intended to investigate frequency and diversity of CYPs from M. ulcerans strains, understand the pan-CYPome clustering patterns and interconnection of CYPs using bioinformatics tools. M. ulcerans strains demonstrated the presence of 261 CYPs categorized into 35 families and 38 subfamilies. CYP138, CYP140, CYP189 and CYP125 were the ﬂourishing families. Around, 20 CYP families and 20 subfamilies were conserved. Flourishing and conserved CYP families/subfamilies were associated with lipid metabolism, substrate utilization etc. CYP140 had a role in pathogenesis. CYP279 was the least dominant family. CYP135, CYP183, CYP190, CYP271 and CYP276 were diagnostic markers for M. ulcerans subsp. shinshuense strain ATCC 33728 and M. ulcerans strain P7741. The pan-CYPome specified that M. ulcerans is evolving by gaining CYPs. CYP centric clustering revealed diversity and resemblances among M. ulcerans strains. More diverse nature of the M. ulcerans strain Harvey could be attributed to its larger size and geographical location. Co-occurrence network demonstrated mutual associations amongst substantial number of CYP families/subfamilies. This work provided comprehensive understanding of previously unexplored CYPs from M. ulcerans.